Design, Synthesis, and Analysis of Minor Groove Binder Pyrrolepolyamide-2′-Deoxyguanosine Hybrids. (22nd December 2009) - Kawashima, Etsuko; Ohba, Yusuke; Terui, Yusuke; Kamaike, Kazuo
Abstract : Pyrrolepolyamide-2 ′ -deoxyguanosine hybrids (Hybrid2 and Hybrid3 ) incorporating the 3-aminopropionyl or 3-aminopropyl linker were designed and synthesized on the basis of previously reported results of a pyrrolepolyamide-adenosine hybrid (Hybrid1 ). Evaluation of the DNA binding sequence selectivity of pyrrolepolyamide-2 ′ -deoxyguanosine hybrids was performed by CD spectral andT m analyses. It was shown that Hybrid3 possessed greater binding specificity than distamycin A, Hybrid1 and Hybrid2 .